A novel nail-plate construct for the treatment of AO/OTA 31-A3.3 intertrochanteric fractures: a finite element analysis - Fan, Jixing; Cao, Yuan; Cui, Zengzhen; Gao, Shan; Lv, Yang; Zhou, Fang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe AO/OTA 31-A3.3 is the most unstable type with a lesser trochanteric fragment and a broken lateral femoral wall (LFW), which constitute a four-part unstable intertrochanteric fracture. Implant failure remains one of the catastrophic consequences after surgical treatment. A novel nail-plate construct, called proximal femoral universal nail system (PFUN), is proposed by our team to fix comminuted LFW fracture fragment and lesser trochanteric fragment. The aim of this study is to evaluate the biomechanical properties of PFUN compared with proximal femoral nails anti-rotation (PFNA) for the treatment of AO/OTA 31-A3.3 intertrochanteric fractures.MethodsAn AO/OTA 31-A3.3 intertrochanteric fracture model was established by computed tomography images. The models of implant (PFUN and PFNA) were created and virtually inserted into the A3.3 fracture model. The von Mises stress on the proximal femur, fracture end, implant and the total displacement of the device components were evaluated and compared for both PFUN and PFNA models.ResultsThe maximum von Mises stress in the proximal femur of the PFNA model increased by 85.81% when compared with the PFUN model in A 3.3 intertrochanteric fractures. The peak von Mises stress was located at the medial-inferior part of the fracture ends in the PFUN and PFNA models and the maximum von Mises stress in the PFUN model and PFNA model was 27.27 MPa and 49.95MPa, respectively. The PFUN model and PFNA model had similar peak von Mises stress in the implant. Furthermore, the maximum displacement in the PFUN model was much smaller than that in the PFNA model.ConclusionThe PFUN exhibited a lower peak von Mises stress in the proximal femur and fracture end, and a smaller maximum model displacement than PFNA in A3.3 intertrochanteric fractures. Our findings might provide valuable references for clinical decision making in surgical treatment of complex intertrochanteric fractures.